Guided growth for angular correction in children: a comparison of two tension band plate designs. Issue 1 (January 2018) - Kadhim, Muayad; Gauthier, Luke; Logan, Karl; El-Hawary, Ron; Orlik, Benjamin
Abstract : This retrospective cohort study examined 20 patients (48 physes), 11 boys and nine girls, who were treated with hinge-plate or eight-plate. The mean age of the patients at surgery was 11.9±2.6 years. The mean follow-up duration was 13±2.7 months. The radiographic measurement of both distal femoral and proximal tibial deformity showed significant correction, with no difference between the hinge-plate and the eight-plate. Both screw divergence angle and the hinge angle showed significant changes at the last follow-up. The deformity correction of the distal femoral physis was quicker than the proximal tibial physis. The rate of mechanical femoral–tibial angle correction was 0.97°/month if both femoral and tibial physes were treated. Level of evidence: III.